The associations among gratitude, job crafting, teacher-student relationships, and teacher psychological well-being - Zheng, Xue; Huang, Hezi; Yu, Quanda (Frontiers in Psychology, 2024)
Introduction: This study explores the complex dynamics among gratitude, job crafting, teacher psychological well-being, and teacher-student relationships within the context of Chinese English as a Foreign Language (EFL) teachers. Methods: A sample of 456 Chinese EFL teachers participated in this study. Valid scales were administered to collect data on gratitude, job crafting, teacher psychological well-being, and teacher-student relationships. Structural Equation Modeling (SEM) was employed to investigate these relationships. Results: The findings reveal significant connections between gratitude, job crafting, teacher psychological well-being, and teacher-student relationships. SEM analysis demonstrates that gratitude and job crafting have direct effects on teacher psychological well-being. Furthermore, teacher-student relationships were identified as a mediator in these relationships. Discussion: This study underscores the importance of gratitude and job crafting in enhancing the psychological well-being of EFL teachers. It highlights the mediating role of positive teacher-student relationships in the associations between gratitude, job crafting, and teacher psychological well-being. These results have implications for the development of interventions and practices aimed at promoting gratitude, job crafting, and positive teacher-student relationships in the EFL teaching context.